Analisis Kebutuhan Pengembangan Bahan Ajar Biologi SMA Berbasis Etnosains pada Pengolahan Kopi di Jember - Adinda Ayu Anggelya; Kukuh Munandar; Agus Prasetyo Utomo (CV. ULIL ALBAB CORP, 2025)
Teaching materials are all forms of documents or sources of information that are used to support learning and help students understand the concepts of the material. Also, as time goes by, teaching materials are needed that are interesting and can also be integrated with technology. So it is necessary to analyze the needs of teachers and students to find out the teaching materials needed by teachers and students in the learning process. This research aims to analyze the needs of teachers and students regarding the development of biology teaching materials, especially ethnoscience-based biodiversity material in State High Schools. 2 Jember. The method used is a qualitative descriptive method. Data collection was carried out using observation and interview methods, with research instruments in the form of teacher questionnaires. The data analysis used is by reducing the data from observations and interviews into more specific data to be presented descriptively. The research results show that teachers and students need teaching materials that are interesting and easily accessible. The development of ethnoscience-based e-modules is still rarely carried out by teachers, even though it can enrich biology learning with multimedia and local values, as well as expand the variety of teaching materials available. Therefore, it can be concluded that it is necessary to develop ethnoscience-based e-modules to explain concepts biology regarding coffee, especially the processing process with technological support, in order to improve learning and the relevance of coffee material at Jember High School.